HUBUNGAN ANTARA DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN SUBJECTIVE WELL-BEING PADA SANTRI YANG TINGGAL DI PONDOK PESANTREN - Ainur Faizah; Widyastuti Widyastuti (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
This study aims to determine the relationship between peer social support and subjective well-being in students who live in boarding schools. This study uses a correlational quantitative approach. The population in this study amounted to 158 and a sample of 108 using probability sampling technique with simple random sampling type. This research instrument is the Satisfaction with Life Scale (SWLS) to measure the cognitive component and the Scale of Positive and Negative Experience (SPANE) with a reliability of 0.887 to measure subjective well-being. While peer social support was measured using the Peer Social Support Scale with a reliability of 0.876. The data in this study used Pearson's product moment correlation. The results show that there is a significant positive relationship between peer social support and subjective well-being with a sig value. 0,004 (p<0,05).